2005
DOI: 10.1292/jvms.67.943
|View full text |Cite
|
Sign up to set email alerts
|

A Canine Pemphigus Foliaceus Case Showing Parallel Relationship of Disease Activity and Titer of Serum Anti-keratinocyte Cell Surface Antibodies

Abstract: ABSTRACT. A seven-year-old, spayed female mongrel dog was diagnosed as pemphigus foliaceus (PF) by clinical, histopathological and immunopathological observations. Serum antibodies against the cell surface of keratinocytes in the dog were detected by indirect immunofluorescence (IIF) using cryosectioned bovine esophagus as well as living cultured-canine keratinocytes as the substrates. When we compared the titers of IIF on bovine esophagus with its disease activity, the IIF titers reflected the disease activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…No correlation was shown between antibody titres and APP concentrations in different infectious diseases . Contrary to the findings of other studies, we found a weak positive correlation between CRP values with the IIF antibody titres in dogs with PF, possibly because PF is a chronic disease that may have periods of acute exacerbation …”
Section: Discussioncontrasting
confidence: 99%
“…No correlation was shown between antibody titres and APP concentrations in different infectious diseases . Contrary to the findings of other studies, we found a weak positive correlation between CRP values with the IIF antibody titres in dogs with PF, possibly because PF is a chronic disease that may have periods of acute exacerbation …”
Section: Discussioncontrasting
confidence: 99%
“…In six dogs, immunosuppression led to a reduction in clinical scores with serum IgG, IgG1 and IgG4 autoantibody titres decreasing in four, one and four patients, respectively 59 . Similarly, serum titres of IgG autoantibodies correlated with the severity of clinical signs of canine PF in two recent reports from the same group 22,60 …”
Section: Pemphigus Foliaceusmentioning
confidence: 61%
“…In dogs with PF, appropriate substrates for indirect IF have been reported to be bovine oesophagus 13 and dog keratinocyte cultures 14,15 . Using one of these substrates, Nishifuji and colleagues established that IgG autoantibody titres correlated with clinical disease in one dog with PF 16 …”
Section: Introductionmentioning
confidence: 99%